The use of respondent incentives on longitudinal surveys - Heather Laurie; Peter Lynn (University of Essex, Institute for Social and Economic Research (ISER), 2008)
Incentives in the form of a gift or money are given to survey respondents in the hope that this will increase response rates and possibly also reduce non-response bias. They can also act as a means of thanking respondents for taking part and showing appreciation for the time the respondent has given to the survey. There is a considerable literature devoted to the effects of respondent incentives, though most studies are based on cross-sectional surveys. These studies show that the both the form of the incentive, gift or money, and the way in which the incentive is delivered to the respondent has a measurable impact on response rates. A monetary incentive sent to the respondent in advance of the interview has the greatest effect on increasing response, regardless of the amount of money involved. This type of unconditional incentive is thought to operate through a process of social reciprocity where the respondent perceives that they have received something unconditionally on trust so reciprocate in kind by taking part in the research. Some of the literature suggests an improvement in data quality from respondents who are given an incentive, in terms of reduced item non-response and reduced bias through encouraging certain demographic groups to participate who otherwise might refuse. It is generally felt that incentives are more appropriate the greater the burden to respondents of taking part. Longitudinal surveys certainly constitute high burden surveys, but there is little guidance on how and when incentives should be employed on longitudinal surveys. In this paper, we review the use that is made of incentives on longitudinal surveys, describing common practices and the rationale for these practices. We attempt to identify the features of longitudinal surveys that are unique and the features that they share with cross-sectional surveys in terms of motivations and opportunities for the use of incentives and possible effects of incentives. We then review experimental evidence on the effects of incentives on longitudinal surveys. Finally, we report on two experimental studies carried out in the UK. These both address a particular issue in longitudinal surveys, namely the effect of changing the way that incentives are used part-way through the survey. Each experiment addressed a different type of change. The first experiment was carried out on the British Election Panel Survey, where an incentive was introduced for the first time at wave 6. Three experimental groups were used at both waves 6 and 7, consisting of a zero incentive and two different values of unconditional incentive. The second experiment was carried out on wave 14 (2004) of the British Household Panel Survey (BHPS). BHPS respondents have always received a gift token as an incentive and since wave 6 of the study (1996) this has been offered unconditionally in advance of the interview to the majority of respondents. The wave 14 experiment was designed to assess the effect on response of increasing the level of the incentive offered from 7 to 10 for established panel members, many of whom have co-operated with the survey for thirteen years.
Keywords: 330